Aplikasi media pembelajaran pendidikan agama islam dan budi pekerti kelas VI(studi kasus : SDIT Ath-Thaariq Muhammadiyah Dumai): Application of learning media for Islamic religious education and ethics (case study: sdit ath-tharayq muhammadiyah dumai) - zakia, zakia; Yuliati, Tri; Desriyati, Welly (Sekolah Tinggi Teknologi Dumai, 2024)
Learning is a communication process between learners, teachers and teaching materials. Communication will not work without the help of a means of delivering messages or media. Currently, the delivery of learning messages from teachers to students still uses teaching aids such as books. Learning media is a teaching aid for teachers to convey teaching material, increase student creativity and increase student attention in the learning process. Learning media can help teachers simplify the process of students' understanding of the delivery of lesson material. Sdit Ath-Thaariq Muhammadiyah Dumai is a private school with A accreditation in the city of Dumai. Sdit Ath-Thaariq Muhammadiyah Dumai in carrying out the learning process is usually given in the form of print media. Learning through print media is still considered less effective and lacks understanding in every student's comprehension and memory. Therefore, we need a learning application media that can change learning from print media to digital media. This research applies the MDLC method which is an appropriate method for designing and developing learning media which is a combination of image, sound, video and animation media. This research produces a learning media application in the form of image, sound, video and 2D animation media which can increase students' interest and enthusiasm in receiving learning at Sdit Ath-Thaariq Muhammadiyah Dumai with a percentage of feasibility of success in learning media through a questionnaire distributed to 26 students and 1 class VI teacher in the subjects of Islamic religious education and character produced a percentage of 86.8462% of the total 100%.